A Critical Ear: Analysis of Value Judgments in Reviews of Beethoven's Piano Sonata Recordings - Alessandri, Elena; Williamson, Victoria J.; Eiholzer, Hubert; Williamon, Aaron (Frontiers in Psychology, 2016)
What sets a great music performance apart? In this study we addressed this question through an examination of value judgements in written criticism of recorded performance. One hundred reviews of recordings of Beethoven’s piano sonatas, published in the Gramophone between 1934 and 2010, were analyzed through a three-step qualitative analysis that identified the valence (positive/negative) expressed by critics’ statements and the evaluation criteria that underpinned their judgements. The outcome is a model of the main evaluation criteria used by professional critics: aesthetic properties, including intensity, coherence, and complexity, and achievement-related properties, including sureness, comprehension, and endeavor. The model also emphasizes how critics consider the suitability and balance of these properties across the musical and cultural context of the performance. The findings relate directly to current discourses on the role of evaluation in music criticism and the generalizability of aesthetic principles. In particular, the perceived achievement of the performer stands out as a factor that drives appreciation of a recording.